2021
DOI: 10.3390/jcm10163656
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Immunosuppression Strategy in the Sensitized Kidney Transplant Recipient

Abstract: Patients with previous sensitization events against anti-human leukocyte antigens (HLA) often have circulating anti-HLA antibodies. Following organ transplantation, sensitized patients have higher rates of antibody-mediated rejection (AMR) compared to those who are non-sensitized. More stringent donor matching is required for these patients, which results in a reduced donor pool and increased time on the waitlist. Current approaches for sensitized patients focus on reducing preformed antibodies that preclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 160 publications
0
6
0
Order By: Relevance
“… 19 Use of primary nonsensitized adult recipients and appropriate immunosuppression was associated with improved graft survival. 20 Previous reviews of functional isotopic renography of allografts from donors <15 kg showed an initial rapid growth, followed by continuous growth and attaining adult volume within 18 months. 21 …”
mentioning
confidence: 99%
“… 19 Use of primary nonsensitized adult recipients and appropriate immunosuppression was associated with improved graft survival. 20 Previous reviews of functional isotopic renography of allografts from donors <15 kg showed an initial rapid growth, followed by continuous growth and attaining adult volume within 18 months. 21 …”
mentioning
confidence: 99%
“…Optimal immunosuppression: Research on determining the most effective immunosuppressive regimens that balance graft protection and infection risk reduction is critical. Optimizing immunosuppression is a complex challenge in the care of transplant recipients, and understanding the best approaches can lead to improved patient outcomes and reduced UTI risk [ 79 ].…”
Section: Reviewmentioning
confidence: 99%
“…Patients with previous sensitization events against antihuman leukocyte antigens (HLA) often have circulating anti-HLA antibodies [7]. Following organ transplantation, sensitized patients have higher rates of antibody-mediated rejection (AMR) compared to those who are non-sensitized.…”
Section: Graft Failurementioning
confidence: 99%